Effectiveness of a WeChat-based personalized rehabilitation nursing model for urinary incontinence after prostatectomy: a retrospective cohort study - Chen, Sijin; Zhang, Ruochen; Zou, Zijun; Yang, Yaojing; Lin, Le; Ye, Liefu; Wu, Jinfeng; Zhang, Yuanman; Song, Wei; Wei, Qichen; Wei, Yongbao (Frontiers in Oncology, 2025)
Postoperative urinary incontinence (UI) is one of the most common complications affecting the quality of life in prostate cancer patients. Traditional nursing models mainly rely on outpatient guidance, making it difficult to provide continuous and dynamic rehabilitation support, and patient compliance is generally low. A personalized nursing model based on the WeChat platform offers a new strategy for managing postoperative UI through real-time interaction, training delivery, and individualized feedback. This study enrolled 123 patients with postoperative UI after radical prostatectomy, divided into a WeChat education group (n=65) and a traditional nursing group (n=58). Baseline characteristics, including UI severity and quality of life scores, were comparable between groups. After six months of follow-up, the WeChat group showed a 120 mL reduction in 24-hour urine leakage, an average decrease of 5.8 points in ICIQ-SF score, and an improvement of 0.18 in EQ-5D score—all significantly better than the traditional group (P<0.01). The WeChat group also demonstrated higher compliance (92%) and nursing satisfaction scores (9.2/10) than the traditional group (P<0.01). Multivariate linear regression analysis identified compliance, initial urine leakage volume, and age as independent predictors of UI improvement, while surgical approach and lymph node dissection were not significantly associated. These findings suggest that the WeChat-based nursing model effectively improves postoperative urinary continence and quality of life, offering a scalable, efficient, and individualized digital nursing strategy for managing UI after prostatectomy.